An Investigation of How Basic Education Level Explains the Phenomena of Unemployment Differently in Urban and Rural Areas - Sari Melati , Inaya; Andriani Setyowati, Fitri (KnE Social Sciences, 2020)
This study aims to determine the effect of basic education level on unemployment and poverty rate based on the classification of urban and rural areas. The data were taken from Wonosobo Regency as the poorest district in Central Java, Indonesia, with the percentage of poor population of 20.32%. Using descriptive quantitative and linear regressions with dummy variable, we analyzed the distinguished effect of basic education level towards unemployment and poverty rate between urban and rural areas. The results show that, generally, basic education level affected unemployment and poverty rate. The basic education level affected unemployment rate in both urban and rural areas. However, the basic education level in urban area did not have an effect as significant as that in rural area in affecting poverty rate. Urban people faced more competitive workforce market that made them need more than just the basic education. Therefore, even most of them had finished their primary and secondary school; it did not mean they are not going to be trapped in poverty. Meanwhile, the basic education of rural people affected the poverty rate as the more people did not finish their basic studies; the more people had no eligibility in doing proper jobs to achieve the wealth. Keywords: basic education level, poverty, rural area, unemployment, urban area